The impact of problem-based learning on Chinese-speaking elementary school students' English vocabulary learning and use. (December 2015) - Lin, Lu-Fang
Abstract: This study examined the impact of the problem-based learning (PBL) approach on English vocabulary learning and use in an elementary school in Taiwan. Two classes, each with 28 students, participated in the study. One class was assigned to be the experimental group and the other the control group. Both groups received the same learning content, but different instructional input. The experimental group used the PBL technique and learned the target vocabulary through learner-centered activities, while the control group used teacher lecture-based instructional techniques. All participants completed pre- and post-tests on vocabulary knowledge and wrote a topic-based composition and a self-report. The t-test results of the pre- and post-tests show that there were no significant differences between the two groups. However, the PBL group outperformed the non-PBL group in using the Off-List level of vocabulary in the writing task. The PBL participants also used a significantly higher proportion of vocabulary beyond the 2000-word level, and wrote significantly longer compositions than their counterparts. The PBL participants' self-reports suggest that PBL provided sufficient English conversation practice; it can be used to foster elementary school students' ability to learn and use vocabulary in context.